2021
DOI: 10.3390/ijms222312706
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Impair Cognitive Functions and Modify the Hippocampal Level of Neurotransmitters in a Coating-Dependent Manner

Abstract: Due to their potent antibacterial properties, silver nanoparticles (AgNPs) are widely used in industry and medicine. However, they can cross the brain–blood barrier, posing a risk to the brain and its functions. In our previous study, we demonstrated that oral administration of bovine serum albumin (BSA)-coated AgNPs caused an impairment in spatial memory in a dose-independent manner. In this study, we evaluated the effects of AgNPs coating material on cognition, spatial memory functioning, and neurotransmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Results obtained by Recordati et al showed high deposition of silver in the brain after oral exposure of environmentally relevant dose of citrate-coated AgNPs at the end of the administration as well as after 4 weeks of recovery that highlighted slow elimination of Ag from the brain structures [23]. Our previous study has also shown that oral administration of AgNPs at a relatively small concentration resulted in a time-dependent accumulation of silver in the brain, particularly in the hippocampus, and simultaneous deterioration of learning skills in rats [16,24]. Additionally, our recent studies demonstrated that the effect of AgNPs on cognitive functions is determined by the coating used for the stabilization of these nanoparticles.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Results obtained by Recordati et al showed high deposition of silver in the brain after oral exposure of environmentally relevant dose of citrate-coated AgNPs at the end of the administration as well as after 4 weeks of recovery that highlighted slow elimination of Ag from the brain structures [23]. Our previous study has also shown that oral administration of AgNPs at a relatively small concentration resulted in a time-dependent accumulation of silver in the brain, particularly in the hippocampus, and simultaneous deterioration of learning skills in rats [16,24]. Additionally, our recent studies demonstrated that the effect of AgNPs on cognitive functions is determined by the coating used for the stabilization of these nanoparticles.…”
Section: Discussionmentioning
confidence: 82%
“…The behavioral test used to assess learning skills in these rats revealed impaired formation and consolidation of memory traces in the AgNPs(BSA)-treated group. The effects of this impairment were shown to be deficits of memory acquisition and maintenance of long-term memory [24]. Other authors also observed steroid-related behavioral disorders, including anxiety-like behavior in mice exposed to citrate-coated AgNPs [45].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Platelets (PLT) are circulatory guards in the blood stream and have chemotactic effects on damaged vasculature and tumor tissue. Recent studies have shown that PLT membranes can be used as biomimetic coatings Figure 4 , ( Jiang et al, 2020 ; Dziendzikowska et al, 2021 ). Plasma membranes derived from human platelets have a variety of proteins, glycoproteins, and lipids and possess platelet-like properties, such as the ability to avoid macrophage recognition, capture of circulating tumor cells, and homing to inflammatory sites ( Dziendzikowska et al, 2021 ).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Recent studies have shown that PLT membranes can be used as biomimetic coatings Figure 4 , ( Jiang et al, 2020 ; Dziendzikowska et al, 2021 ). Plasma membranes derived from human platelets have a variety of proteins, glycoproteins, and lipids and possess platelet-like properties, such as the ability to avoid macrophage recognition, capture of circulating tumor cells, and homing to inflammatory sites ( Dziendzikowska et al, 2021 ). Bahmani et al reported the development of a PLTs-membrane coated nanoparticle (PNP) specifically designed for intratumoral delivery of resiquimod (R848) to treat solid tumors ( Bahmani et al, 2021 ).…”
Section: Nanoparticlesmentioning
confidence: 99%